Acute Pulmonary Hypertension During Pregnancy Caused by Isolated Cor Triatriatum Sinus With Left Atrial Thrombus. (August 2019) - Ji, Li; Wu, Wenqian; Sun, Zhenxing; Wang, Bin; Lv, Qing; Li, Yuman; Zhang, Li; Xie, Mingxing
Abstract : Supplemental Digital Content is available in the text.